ANALISIS PENERIMAAN QRIS DI KALANGAN UMKM - Alfiana Alfiana; Nika Sintesa; Toto Heru Dwihandoko; Eko Budi Lestari; Nersiwad Nersiwad (JURNAL LENTERA BISNIS, 2025)
The purpose of this study is to analyze the acceptance of QRIS among MSMEs. This research approach collects data through literature studies, which involve reading literature from various sources including books, articles, journals and reports using qualitative and deductive approaches. The findings in this study are that the acceptance of QRIS among MSMEs has benefits and positive impacts in simplifying and accelerating the payment system, facilitating monitoring and analyzing transaction history and financial arrangements, improving merchant business performance, developing MSME growth, encouraging efficiency in the economic sector, and accelerating inclusive finance. However, there are still obstacles such as unstable internet connections, security issues and transaction readability, and admin deductions on QRIS. Therefore, with the right strategy, such as education and training, improving digital infrastructure, promotion and incentives, and improving system security, QRIS can be more widely accepted and utilized by MSMEs.